2001
DOI: 10.1063/1.1372976
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial stress dependence of the binding energy of shallow donor impurities in GaAs–(Ga,Al)As quantum dots

Abstract: We have studied the effects of an uniaxial stress on the binding energy of a shallow donor impurity in a parallelepiped-shaped GaAs–(Ga,Al)As quantum dot. In the calculations we have used a variational technique within the effective-mass approximation. The stress was applied in the z direction and the donor impurity was located at various positions along the z axis. Our results show that the donor binding energy increases with increasing stress and for decreasing sizes of the quantum dot. Also, we have found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…In the last two decades many works related with the magnetic fields effects on the properties of the electron-impurity systems have been reported in GaAs − Ga 1−x Al x As quantumwell wires (QWWs) and quantum dots (QDs) [4][5][6]. The effects of hydrostatic pressure on such systems, and in particular on the photoionization (PI) cross-section, show that the PI depends strongly on the symmetry of the potential that confines the carriers, of the energy of the incident photon, and of the impurity distribution inside the heterostructure [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades many works related with the magnetic fields effects on the properties of the electron-impurity systems have been reported in GaAs − Ga 1−x Al x As quantumwell wires (QWWs) and quantum dots (QDs) [4][5][6]. The effects of hydrostatic pressure on such systems, and in particular on the photoionization (PI) cross-section, show that the PI depends strongly on the symmetry of the potential that confines the carriers, of the energy of the incident photon, and of the impurity distribution inside the heterostructure [7].…”
Section: Introductionmentioning
confidence: 99%
“…(1) without the impurity potential term and the eigenvalue associated with the wave function in Eq. (3) minimized with respect to the variational parameter λ [9].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Elabsy [4] has calculated the effects of the hydrostatic pressure on the binding energy of donor impurities in quantum well heterostructures, finding that the binding energy increases with increasing external hydrostatic pressure for a given quantum well thickness and temperature. Oyoko et al [9] have studied the effects of a uniaxial stress on the binding energy of shallow donor impurities in parallelepiped-shaped GaAs/GaAlAs QDs. They have found that the binding energy increases almost linearly with applied stress and diminishes with the sizes of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of an electric field on the electronic states and binding energy of a hydrogenic impurity in QD's is considered in [21,27], and the uniaxial stress dependence of the binding energy of shallow donor impurities in a parallelepiped-shaped QD is studied in [28]. It was shown that the binding energy increases with increasing stress of the QD and also with the proximity of the impurity to the center of the QD.…”
Section: Introductionmentioning
confidence: 99%